1979
DOI: 10.1002/bip.1979.360180421
|View full text |Cite
|
Sign up to set email alerts
|

Compressibility studies of three proteins in CsCl solutions in the analytical ultracentrifuge

Abstract: [article in Biopolymers 17,817-836 (1978)] Previously reported' standard pressure coefficients (Go) and standard partial specific volumes of the solvated component (i&) for egg albumin (EA), pooled human y-immunoglobulin (IgG), and bovine serum mercaptalbumin (BMA) are in error. These errors are due to the incorrect use of the formula2 to calculate the quantity ( r f -r:). The effect of using the correct expression for (r: -r:) is to substantially decrease in magnitude Ap-especially a t high angular velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1979
1979
1982
1982

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Similarly, PEDERSEN et al (18) in the following article in this journal have observed an increase in the hydration of the ~charge-ion complexes,, of ovalbumin as a function of water activity. However, the analysis by SHARP et al (25) of the data of BULL and BREESE (2) indicates no change in the hydration of egg albumin with av…”
Section: Hydrations and Water Activitiesmentioning
confidence: 99%
“…Similarly, PEDERSEN et al (18) in the following article in this journal have observed an increase in the hydration of the ~charge-ion complexes,, of ovalbumin as a function of water activity. However, the analysis by SHARP et al (25) of the data of BULL and BREESE (2) indicates no change in the hydration of egg albumin with av…”
Section: Hydrations and Water Activitiesmentioning
confidence: 99%
“…(2)- (4) that numerical and iterative computational techniques are needed to describe the various distributions and unknown parameters.…”
Section: Methodsmentioning
confidence: 99%
“…These methods are described in a previous paper. 2 Accounting for pressure effects that alter the composition gradient involves an additional expression for pressure, and alters the expression for the density gradient represented by Eq. (1).…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation